2023
DOI: 10.1097/md.0000000000034125
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to sofosbuvir-based therapy using serum interleukin-12 and single nucleotide polymorphism of the interleukin 28B gene as predictive factors in HCV positive genotype-4 patients

Doaa Mohamed Abdelnajid,
Ahmed Y. Elmowafy,
Lionel Rostaing
et al.

Abstract: Some hepatitis-C virus patients have resistance to direct-acting-antivirals (DAAs). Genetic polymorphisms have been associated with drug resistance. This study aimed to evaluate the role of interleukin (IL)-28B gene polymorphism and IL-12 levels as predictors for a response to sofosbuvir/ribavirin (SOF/RBV) with (triple-therapy) or without (dual-therapy) Peg-alpha-interferon. 92 hepatitis C virus (HCV)/RNA (+)-patients treated with dual (n = 72) or triple (n = 20) therapy. IL28B genetic polymorphism and IL-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Several studies have found an association between the host genetic factor, spontaneous clearance of the virus, the treatment response and the risk of fibrosis and/or hepatocarcinoma. Most studied single nucleotide polymorphisms (SNPs) are from the IL28B gene; however, several other SNPs in different genes have been involved: interferon-λ3, interferon-λ4, IL-12, TNF, IL-10 and Toll-like receptors 3 and 9 [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]. Moreover, a relationship has been recently shown between increased mortality and epigenetic changes related to age in a group of intravenous drug users coinfected with HCV-HIV [147].…”
Section: Host Genetics Infection and Response To Hcv Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found an association between the host genetic factor, spontaneous clearance of the virus, the treatment response and the risk of fibrosis and/or hepatocarcinoma. Most studied single nucleotide polymorphisms (SNPs) are from the IL28B gene; however, several other SNPs in different genes have been involved: interferon-λ3, interferon-λ4, IL-12, TNF, IL-10 and Toll-like receptors 3 and 9 [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]. Moreover, a relationship has been recently shown between increased mortality and epigenetic changes related to age in a group of intravenous drug users coinfected with HCV-HIV [147].…”
Section: Host Genetics Infection and Response To Hcv Treatmentsmentioning
confidence: 99%
“…Patients with the SNP rs12979860 CC polymorphism are more likely to achieve an SVR at 12 weeks of treatment with sofosbuvir/daclastavir in genotype 4-infected Egyptian patients [136]. This gene has been studied both as a predictor of response and as a factor of resistance to treatment in patients treated with sofosbuvir, raising the possibility of performing genetic analysis for the SNP in IL-28B before initiating antiviral treatment [139,140].…”
Section: Host Genetics Infection and Response To Hcv Treatmentsmentioning
confidence: 99%